2000
DOI: 10.1128/aac.44.4.967-971.2000
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Resistance Genes in Enterococcus spp

Abstract: Seventy-eight isolates of different Enterococcus species (E. faecalis, n ‫؍‬ 27; E. faecium, n ‫؍‬ 23; E. durans, n ‫؍‬ 8; E. avium, n ‫؍‬ 6; E. hirae, n ‫؍‬ 9; E. gallinarum, n ‫؍‬ 3; and E. casseliflavus, n ‫؍‬ 2) with a variety of erythromycin resistance phenotypes were examined for the presence of macrolide resistance genes (ermA, ermB, ermC, ermTR, mefA/E, and msrA). Positive PCR amplifications of ermB were obtained for 39 of 40 highly erythromycin-resistant Enterococcus isolates (MICs, >128 g/ml) of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(139 citation statements)
references
References 30 publications
12
121
2
4
Order By: Relevance
“…in different Enterococcus spieces have been described in recent studies (Jost et al, 2004;Luna et al, 1999;Portillo et al, 2000). As claimed by Portillo et al (2000), the most commonly erm class found in streptococci and enterococci is erm(B) class, followed by erm (TR), a subset of erm(A) class.…”
Section: Erm(a) Erm(b) Erm(c) Erm(f))mentioning
confidence: 98%
See 2 more Smart Citations
“…in different Enterococcus spieces have been described in recent studies (Jost et al, 2004;Luna et al, 1999;Portillo et al, 2000). As claimed by Portillo et al (2000), the most commonly erm class found in streptococci and enterococci is erm(B) class, followed by erm (TR), a subset of erm(A) class.…”
Section: Erm(a) Erm(b) Erm(c) Erm(f))mentioning
confidence: 98%
“…Enterococci are potential pathogens and they are becoming resistant and have acquired resistant genes to withstand the effects of antibiotics Butaye et al, 2001;Portillo et al, 2000;Thal et al, 1995;Yuri. et al, 2005).…”
Section: Antibiotic Resistance In Enterococcimentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that resistance against these antibiotics has been connected with transferable genetic elements [34,65]. The appearance of resistant enterococci that might carry such elements (plasmids, transposons) gives rise to a very large discussion about the health risks posed by the dissemination of these genetic elements in the environment through the reuse of treated waste (manures and sewage sludge).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Over the last decade, enterococci have been implicated in nosocomial infections worldwide. Due to their ability to acquire high-level resistance to antimicrobial agents such as vancomycin and erythromycin, they have become a serious threat for public health [33,34].…”
Section: Introductionmentioning
confidence: 99%